El derecho de manifestación ante el Parlamento - Santaolalla López, Fernando (Revista de Derecho Político, 2014)
Summary: 1. Justification of the present commentary. 2. The importance of the right of pubblic assembly and demonstration before the parliamentary headquarters. 3.Reference to the solution adopted in other countries. 4. The right of demonstration in front of the British Parliament. 5. The right of demonstration before the Congress of Deputies, the Senate and territorial parliaments. ADDENDA. The decision 31/2014, of 7 July, of the Audiencia Nacional, on the demonstration violent before the catalan Parliament. Resumen: Se expone la problemática de las manifestaciones ante el Parlamento, cuestión en la que se hace necesario garantizar tanto el ejercicio de un derecho fundamental como la normal actividad de esta institución. Se estudia la regulación vigente en el Reino Unido y, tras una breve referencia a la situación de otros países, se analiza la situación española. En este punto se comprueba que tanto la legislación vigente como la proyectada resultan claramente insuficientes para compatibilizar estas dos exigencias. Más que de salvaguardar el orden público general se trata aquí de proteger el funcionamiento de una institución clave para la democracia como es el Parlamento. Y esto puede requerir normas más precisas. Abstract: This article focuses on the demonstrations before the Parliament. This issue demands to guarantee both the excercise of a fundamental right as well as the normal activity of this institution. It is commented the regulation existing in the United Kingdom and briefly the solution adopted in other Europenan countries. Then the Spanish situation is analyzed. At this point, the outcome is that both the proposed and existing legislation are clearly insufficient to reconcile these two requirements. What is needed more than safeguard the public order general is to protect the functioning of a key institution for democracy such as Parliament. And that may require more precise provisions.